2014
DOI: 10.1002/j.1839-4655.2014.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuating the problem: neoliberalism, commonwealth public policy and housing affordability in Australia

Abstract: This paper argues that the scale of the contemporary housing affordability crisis in Australia is at least partly attributable to the influence of neoliberal ideas over the past three decades. After providing an overview of the nature and scope of the crisis, the process by which housing as a policy problem has been reconceptualised by policy makers and others since the 1970s is examined. This is followed by analysis of the ways in which a number of commonwealth government policies which are ideationally under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Endnotes 1 See Darcy (2009); Gurran & Phibbs (2014); Nicholls (2014); and Rogers & Darcy (2014), for four recent exceptions. 2 See for example, Milligan & Pinnegar (2010); Gilmour & Milligan (2012); and Tomlinson (2012) for approaches that broadly support this attribution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endnotes 1 See Darcy (2009); Gurran & Phibbs (2014); Nicholls (2014); and Rogers & Darcy (2014), for four recent exceptions. 2 See for example, Milligan & Pinnegar (2010); Gilmour & Milligan (2012); and Tomlinson (2012) for approaches that broadly support this attribution.…”
Section: Resultsmentioning
confidence: 99%
“…A second area that requires further analysis is the extensive influence of neoliberal ideology on housing policy (see Burke & Tiernan 2002;Berry 2014; Orchard 2014 for three wide-ranging discussions with reference to Australia). The ideology of neoliberalism has been deployed as a rationale to justify the reduction in funds for public housing and the use of market-based mechanisms to deliver services within government welfare agencies (Nicholls 2014). While the influence of neoliberalism is apparent, it is important to recognise that the market-based reforms and privatisation policies that were in place in the late 1970s can be sourced to other factors such as: demographic shifts, technological innovation, and globalisation processes (see Berry 1988;Hayward 1996).…”
Section: New Avenues For Housing Policy Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…While attempting to address problems of supply, the Commonwealth's efforts to outsource delivery (e.g. to the community housing sector) and to incorporate private finance were seen by some as ‘divest[ing] government of responsibility for a particular policy area while attempting to facilitate market‑based and/or community/private sector solutions’ (Nicholls : 236). In any case, as the government descended into internecine battles over direction and leadership, housing policy was again subject to drift and uncertainty.…”
Section: From Hawke's New Federalism To Howe's Building Better Citiesmentioning
confidence: 99%
“…By 2013, though the ideological frames through which the housing issue was seen had changed (Orchard ), some have suggested that the problems facing policy makers were precisely those that had confronted them at the end of World War II (Yates : 127; Nicholls : 232). Like many of its predecessor coalition governments, Tony Abbott's Liberal‐National Party government sought first to disengage from the Rudd–Gillard legacy (by instituting a series of reviews, including a Commission of Audit that suggested it withdraw entirely from funding), then to subsume the problem within its planned white paper on federation reform.…”
Section: From Hawke's New Federalism To Howe's Building Better Citiesmentioning
confidence: 99%